2010
DOI: 10.1042/bj20100612
|View full text |Cite
|
Sign up to set email alerts
|

Human Pif1 helicase is a G-quadruplex DNA-binding protein with G-quadruplex DNA-unwinding activity

Abstract: Pif1 proteins are helicases that in yeast are implicated in the maintenance of genome stability. One activity of Saccharomyces cerevisiae Pif1 is to stabilize DNA sequences that could otherwise form deleterious G4 (G-quadruplex) structures by acting as a G4 resolvase. The present study shows that human Pif1 (hPif1, nuclear form) is a G4 DNA-binding and resolvase protein and that these activities are properties of the conserved helicase domain (amino acids 206-620 of 641, hPifHD). hPif1 preferentially bound syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
108
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(112 citation statements)
references
References 44 publications
(87 reference statements)
2
108
0
2
Order By: Relevance
“…Thus, it was proposed that PIF1 function is redundant in mammalian cells. Nevertheless, in vitro analysis of purified full-length PIF1 suggested that it bound and unwound DNA structures that might form during DNA replication stress, including structures resembling stalled replication forks (14) or G-quadruplexes (28). The effects of PIF1 depletion on S-phase transition, checkpoint activation, and apoptosis in tumor cells are consistent with these in vitro results; however, nontumor cell lines did not show similar responses.…”
Section: Discussionsupporting
confidence: 79%
“…Thus, it was proposed that PIF1 function is redundant in mammalian cells. Nevertheless, in vitro analysis of purified full-length PIF1 suggested that it bound and unwound DNA structures that might form during DNA replication stress, including structures resembling stalled replication forks (14) or G-quadruplexes (28). The effects of PIF1 depletion on S-phase transition, checkpoint activation, and apoptosis in tumor cells are consistent with these in vitro results; however, nontumor cell lines did not show similar responses.…”
Section: Discussionsupporting
confidence: 79%
“…Experimental Design for Kinetic Characterization of Pif1-mediated G-quadruplex DNA Unwinding-Pif1 was reported previously as a low or nonprocessive helicase for unwinding duplex DNA (19,38,46), but it is highly active for unwinding G4s (19,47). In fact, the G4s do not exist alone as an isolated motif, but instead they are usually connected to double-stranded DNA at one or both sides, such as the G4s implicated in stalled replication forks and in replication origins (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that cells have evolved mechanisms for regulating G4 structures to counteract their intrinsic recombinogenic effects. It has been shown that several helicases such as those in the RecQ (15), DEAH-box (16,17), and Pif families (18,19) possess G4 resolving activity.…”
mentioning
confidence: 99%
“…ScRrm3 also promotes fork progression at other sites where ScPif1 is not known to act, such as at tRNA genes, inactive origins, and the silent mating type loci, while ScPif1 is important for replication through G-rich motifs that can form G-quadruplex structures in vitro (Ivessa et al 2003;Paeschke et al 2011). Human Pif1 (hPif1) also unwinds G-quadruplex structures in vitro, as well as DNA structures that resemble stalled replication forks (George et al 2009;Sanders 2010). Although S. cerevisiae Pif1 family helicases have important roles in DNA replication, pif1D rrm3D cells are viable (Ivessa et al 2000).…”
mentioning
confidence: 99%